Why Astrophysicist Herbert Dingle Rejected Relativity (London Journal of Research In Humanities and Social Sciences, 2025)
Referring to the example of the famous twin paradox, astrophysicist Herbert Dingle argued that Special Relativity is false : two clocks, he said, cannot run slow relatively to each other. His argument implied that the two clocks andtheir readings were real, in accordance with naive realism. It will be shown that they are not real but part of the observers' subjective perception of reality - in which case, nothingprevents them from being different. Thus, it is naive realism which is wrong, not Relativity.
Keywords: educational inclusion; premature baby; child development; learning difficulty; justice.; Fairness; Common Good; Critiques; Justification; special relativity; Reality.; twin paradox; Perception; naive realism